A sonegação fiscal no âmbito do exercício do trabalho dos contadores à luz da banalidade do mal, de Hannah Arendt - Teixeira, Liliane (2018)
It is notorious that tax evasion is a problem of great magnitude in Brazil and that its effects affect society as a whole, including those who practice it, given the commitment of the collection of resources for the maintenance of the State and for the guarantee of the social rights guaranteed to individuals by the Federal Constitution of 1988. Even though tax evasion constitutes a crime against the tax order, it is a common strategy adopted by the organizations. Data from the Sindicato Nacional dos Procuradores da Fazenda Nacional – SINPROFAZ (2017) indicates that the amount that it is not collected because of the evasion is equivalent to 7,5% of the gross domestic product (GDP) of the country. Considering that the organization, as a legal person, is an abstraction, the practice of the delinquent conduct in its name is given by means of a physical person, during the exercise of its work. Inspired by Eichmann in Jerusalem - An account of the banality of evil, a work in which the philosopher Hannah Arendt, recounts the trial of Adolf Eichmann, a nazi bureaucrat who organized the logistics of deportation of Jews to concentration camps, this research aims to identify the perception of professionals in the accounting area about the practice of acts that imply fiscal evasion in the exercise of the profession, associated with the Brazilian way. Eichmann's work was that of a middleman, since he "only" organized the logistics of deporting Jews to concentration camps, where they were decimated. Similarly, the work of accounting professionals can also be used as a means to achieve the ultimate goal of tax evasion. Interviews conducted with two professionals of the area and analyzed using the Content Analysis technique. Among the main results, it was verified that the Brazilian way have a strong influence on the work of accounting professionals, making the non-common, which is tax evasion, take the place of the common, which is the declaration and the collection of taxes in due form, bringing the work of the accountants closer to the lawfulness of Adolf Eichmann and, as a consequence of the banality of evil, since tax evasion is temporized as something "not so wrong", in spite of the consequences it generates for the whole community.